Analysis of the effects of time delay spread on TCM performance. - Pingyi Fan
We investigate the effect of time delay spread on trellis coded modulation (TCM) in a wireless radio environment where equalization is not employed to mitigate the effects of frequency selective fading when the time delay spread is small. Using a random variable decomposition technique and a Gaussian approximation of the intersymbol interference terms, we obtain explicit bounds for the pairwise error probability of TCM over multipath Rayleigh fading channels characterized by various power delay profiles. A method to calculate an upper bound of the bit error rate (BER) based on Jamali and LeNgoc (1995) bound is also presented. These bounds are used to evaluate TCM performance as well as investigate the delay spread tolerance limit of TCM, including I-Q TCM, over frequency selective fading channels
Keywords: BER; Gaussian approximation; I-Q TCM; TCM performance; Bit error rate; Delay spread tolerance limit; Explicit bounds; Frequency selective fading; Frequency selective fading channels; Intersymbol interference; Multipath Rayleigh fading channels; Pairwise error probability; Power delay profiles; Random variable decomposition technique; Time delay spread; Trellis coded modulation; Upper bound; Wireless radio environment